Use of modern contraceptives among married women in Vietnam: a multilevel analysis using the Multiple Indicator Cluster Survey (2011) and the Vietnam Population and Housing Census (2009) - Lan Thi Hoang Vu; Juhwan Oh; Quyen Thi-Tu Bui; Anh Thi-Kim Le (Taylor & Francis Group, 2016)
Background: The prevalence of modern contraceptive use is an important indicator that reflects accessibility to reproductive health services. Satisfying unmet needs for family planning alone could reduce the number of maternal deaths by almost a third. This study uses multiple data sources to examine multilevel factors associated with the use of modern contraceptives among married women in Vietnam aged 15-49 years. Design: Data from different national surveys (Vietnam Population and Housing Census, Vietnam Living Standard Survey, and Multiple Indicator Cluster Survey) were linked to create a dataset including individual and contextual (provincial) variables (N=8,341). Multilevel modeling was undertaken to examine the impact of both individual and provincial characteristics on modern contraceptive use. Odds ratios (ORs) and 95% confidence intervals (CIs) are reported. Results: Individual factors significantly associated with the use of modern contraceptives were age 30-34 years (reference 15-19 years) (OR=1.63); high socioeconomic status (SES) (OR=0.8); having two living children (OR=2.4); and having a son (OR=1.4). The provincial poverty rate mediated the association between the individual's SES and the likelihood of using modern contraceptives. Conclusions: The proportion of women in Vietnam using modern contraceptive methods has remained relatively high in recent years with significant variation across Vietnam's 63 provinces. Women of lower SES are more likely to use modern contraceptive methods, especially in the poorer provinces. Achieving access to universal reproductive health is one of the Millennium Development Goals. Vietnam must continue to make progress in this area.